Cameroon : First Review of the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). (IMF Staff Country Reports; Country Report ;, 2006)
Macroeconomic performance has been satisfactory, and program implementation under the Poverty Reduction and Growth Facility arrangement has also been good. The medium-term projections have been updated in anticipation of relief under the Multilateral Debt Relief Initiative (MDRI). Despite recent steps, governance remains weak. The slowdown in non-oil real growth is a cause for concern and calls for determined actions by the government. Relief under the enhanced Heavily Indebted Poor Countries Initiative and MDRI would reduce Cameroon's debt to sustainable levels.